Overview of the threat of IEMI (intentional electromagnetic interference) - Savage, E.; Radasky, W. (2012 IEEE International Symposium on Electromagnetic Compatibility, 2012)
In this paper we present an overview of the IEMI threat, discuss an assessment approach, and present mitigation options. Because it is often dominant, we concentrate on cable coupling of radiated RF (radio frequency) power as the means of IEMI attack. We separate an IEMI attack into various parts, and introduce an efficient approach for assessing the IEMI vulnerability of a facility. We then present some methods to mitigate IEMI attacks, especially for network cable coupling. Finally, we review ongoing worldwide IEMI efforts.